Peningkatan Pengetahuan Suami Tentang Pendampingan Persalinan Melalui Pemanfaatan E Modul SUMPING (Support Suami Pendamping) - Rahmadona, Rahmadona; Mey Lestanti , Dewi (Jurnal Pengabdian UntukMu NegeRI, 2023)
More than 90% of maternal deaths are caused by complications that often occur during or around childbirth. Childbirth complications are a state of deviation from normal, which directly causes morbidity and death of the mother and baby due to disturbances resulting (directly) from childbirth. Reducing the incidence of birth complications requires the participation of the family (especially husbands), which is in line with government policies and strategies in order to reduce the incidence of birth complications in Indonesia through the Making Pregnancy Safer (MPS) program. The expected result of this strategy is to increase the husband's active role during the pregnancy and birth process. Therefore, the community service implementation team (PKM) of the Midwifery Department, Health Polytechnic of the Ministry of Health, Tanjungpinang, carried out PKM activities with the aim of increasing husbands' knowledge about birth assistance through the use of the E Modul SUMPING (Companion Husband Support). The results of this PKM activity were an increase in husbands' knowledge about birth assistance before and after the SUMPING (Companion Husband Support) e-module was socialized.